Effects of foreign worker on sectorals, skills and labour market outcomes - Abdul Hamid, Kamarul Hidayah (2020)
The expansion of Malaysia’s export-oriented manufacturing and construction sectors in the 1980s was met with serious local labour shortages. As a short-term solution for this conundrum, the government allowed the importation of foreign workers. The absence of a long-term foreign worker policy has however resulted in the influx of unskilled documented and undocumented foreign workers. These workers are claimed by some to affect the economy in a negative way. Though new or improved policies to resolve these challenges are of immense urgency, empirical studies on the impact of foreign workers on the economy and labour market have been shrouded by data inconsistencies lent by weaknesses inherent in labour statistics and clandestine foreign workers, both of which have obscured the exact number of foreign workers. Consequently, these studies have returned ambiguous results, inhibiting the development of effective strategies. To remedy these shortcomings, this study used an improved dataset of foreign workers to (a) analyse the sectoral impact of foreign worker; (b) investigate the effect of foreign worker by skill levels; and (c) investigate the effect of foreign workers on labour market outcomes. In the first objective, the study measured the sectoral impact of foreign worker. Malaysia’s overreliance on foreign workers in certain sectors, such as manufacturing and agriculture, have created much concern about their capability to grow consistently, as these workers are typically unskilled. To measure sectoral employment impact, the study calculated the foreign worker employment multiplier. The results indicate that the largest foreign employment multipliers were in the construction residential, palm oil, and rubber products subsectors. On the other hand, in domestics appliances machinery equipment, manufacture of office, accounting and computing machinery, and manufacture of radio and television subsectors, the inflow of foreign workers would create less than a job. These findings thus suggest that foreign workers have a substantial contribution to the sectors in which they are heavily employed in, but only marginal effects to those otherwise. The second objective was accomplished using the Computable General Equilibrium-Malaysia Foreign Labour Analysis (CGE-MAFLA) model. In this model, labour was disaggregated into four skill types. This exercise produced three important findings. First, the entry of highly skilled foreign workers may help balance the labour market structure. Second, in certain sectors, a competitive relationship exists between highly skilled and skilled workers, and between semiskilled and unskilled workers. Third, the direction and intensity of the impact depends on the nature of the sector itself, such as its specific role in the national economic system and required professional knowledge or skills. Taken together, these results are useful to balance the unbalanced labour market. The entry of highly skilled foreign worker should be encouraged, while unskilled ones must be reduced, as the former has a greater positive impact on local labour demand. In the third objective, the study estimated the impact of foreign workers on two indicators of labour market outcome, namely wage and unemployment rate. The results suggest that an increase of foreign workers of a specific skill group would reduce the wages of local workers of the same group and increase those of complementary groups. An influx of unskilled foreign workers would thus depress the wages of unskilled labourers and increase those of high skilled ones, enlarging the wage gap between the two groups. Surprisingly, semiskilled foreign workers only cause unfavourable effects on semiskilled local labour, while creating favourable effects on the wages of all other skill groups. These results thus suggest that the impact of foreign workers on wages largely depend on their skills. In terms of unemployment, the entry of a specific skill group will increase unemployment within the same group while decreasing that of other groups. An increase of highly skilled foreign workers by four to eight percent reduces total unemployment. On the contrary, the inflow of other skill groups, especially semiskilled, increases domestic unemployment. Altogether, the results imply the necessity to attract skilled foreign workers to and limit unskilled foreign workers from entering the market. To depend on the latter would cause wages to stagnate and displace local workers. The study has produced several policy implications. First, the Malaysian government should prioritise the entry of higher skilled foreign workers into the labour market. The model showed that higher skilled labour could create larger benefits than lower skilled labour in the primary sector and in some tertiary sectors. Second, the policy implication is clear: if the government’s primary objective is to decrease the unemployment rate, the appropriate policy is to encourage the inflow of highly skilled labour. Of all skill groups of foreign workers, only the highlyskilled group is helpful in reducing the total unemployment rate, most likely by creating jobs for the semiskilled and unskilled labour force.